Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

There is a proof in my book I don't quite follow. We are supposed to prove that the Fourier transform of a product of $f$ with $t^n$ is given by

$$\mathcal{F}[t^n f(t)] (\lambda) = i^n \frac{d^n}{d \lambda^n} \{\mathcal{F} [f] (\lambda)\}$$

I will show the proof up until the point I don't get. The proof is:

For the Fourier transform of a product of $f$ with $t^n$, we have

$$\mathcal{F}[t^n f(t)] (\lambda) = \frac{1}{2 \pi} \int_{- \infty}^{\infty} t^n f(t) e^{- i \lambda t} dt$$


$$t^n f(t) e^{-i \lambda t} = (i)^n \frac{d^n}{d \lambda^n} \{f(t) e^{-i \lambda t} \}$$,

we obtain. . .

Now the rest of the proof I understand. However, I don't see where the book gets the expression

$$t^n f(t) e^{-i \lambda t} = (i)^n \frac{d^n}{d \lambda^n} \{f(t) e^{-i \lambda t} \}$$

from. If anyone can explain this to me, I would be very grateful!

share|cite|improve this question
Have you tried figuring out what $\frac{\mathrm d^n}{\mathrm d\lambda}\{f(t)e^{-i\lambda t}\} = f(t)\frac{\mathrm d^n}{\mathrm d\lambda}\{e^{-i\lambda t}\}$ works out to be? Surely you remember $\frac{\mathrm d}{\mathrm d\lambda}\{e^{-i\lambda t}\}=(-it)e^{-i\lambda t}$ from your calculus class? – Dilip Sarwate Jan 11 '13 at 12:59
Thanks! Sorry, I actually tried your suggestion before posting the question, but didn't get the correct answer. Now I see it's because I made a dumb arithmetic mistake. Appreciate it! – Kristian Jan 11 '13 at 13:14
@Kristian I would encourage you to answer your own question and then, after an appropriate amount of time, accept it. – Neal Jan 11 '13 at 13:23
@Kristian I would encourage you to take Neal's advice. – user53153 Jan 12 '13 at 3:04
Thanks for your advice. I have answered my question below. – Kristian Jan 12 '13 at 16:01
up vote 1 down vote accepted

We have:

$$\frac{d}{d \lambda} \{f(t) e^{-i \lambda t} \} = (-it) f(t) e^{- i \lambda t}$$

Differentiating again gives:

$$\frac{d^2}{d \lambda ^2} \{ f(t) e^{- i \lambda t} \} = (-it)^2 f(t) e^{- i \lambda t}$$

So in general:

$$\frac{d^n}{d \lambda ^n} \{ f(t) e^{- i \lambda t} \} = (-it)^n f(t) e^{- i \lambda t}$$

It is now an easy task to check that the two sides of the equation stated in the problem are equal.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.